Social media-based learning: Jane Elisabet’s videos and their effect on learners’ speaking confidence - Zulfa Rona Farchan; Nailul Authar; Savira Zaniar; Tiyas Saputri; Djuwari Sarkawi (Universitas Merdeka Malang, 2025)
In today’s digital era, social media platforms are increasingly leveraged as tools for English language learning. This study investigates the influence of Jane Elisabet’s educational videos on learners’ self-confidence in speaking English. Employing a descriptive qualitative approach, data were gathered through classroom observation and semi-structured interviews with five English Education students who regularly engaged with Jane Elisabet’s video content. The findings indicate notable improvements in learners’ willingness to speak, pronunciation accuracy, and ability to construct basic sentences. Key contributing factors include the simplicity of the language, contextual relevance, and the presenter’s supportive and approachable delivery style. Grounded in Krashen’s Affective Filter Hypothesis, this study emphasizes that reducing anxiety and fostering emotional support can significantly enhance second language acquisition. The results suggest that short, authentic video content on digital platforms not only supports linguistic development but also strengthens learners’ psychological readiness to communicate in English. These findings highlight the potential of social media-based videos as practical supplementary tools in English language education, particularly in boosting learners’ speaking confidence.